PENGEMBANGAN MODUL AJAR BERBASIS MEDIA KOMIK DALAM PEMBELAJARAN FIQH HAJI PADA SISWA KELAS VIII DI MTs MUHAMMADIYAH METRO - ranita purnama; Heri Cahyono; Iswati; Andrianto (PROFETIK: Jurnal Mahasiswa Pendidikan Agama Islam, 2026)
The learning process demands teaching materials that align with competency standards and are relevant to students' needs. Modules, as a form of printed media, play a strategic role because they contain a complete learning unit with supporting components, enabling students to learn independently with minimal teacher guidance. This study aims to answer two main questions: 1) how is the implementation of a comic-based teaching module developed for eighth-grade Hajj fiqh learning for eighth-grade students at MTs Muhammadiyah Metro? And 2) what are the final results of this module development. This study employed a Research and Development (R&D) method with the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The research instruments used were an expert validation sheet to assess the module's feasibility, as well as student and teacher response questionnaires. The data obtained were analyzed descriptively using qualitative and quantitative methods to provide an overview of the implementation and final results of the comic-based teaching module development for eighth-grade Hajj fiqh learning. The results indicate that the implementation of the comic-based teaching module development for eighth-grade Hajj fiqh learning at MTs Muhammadiyah Metro followed the development procedures, involving expert validation and practicality testing. This module received excellent ratings across various aspects, including 89% validation from material experts, 89% validation from design experts, 93% validation from media experts, and 96% validation from language experts, all of which fall into the "very strong" category. Furthermore, the practicality test results showed that teachers gave it an 85% rating and students an 82% rating, both also in the "very strong" category. Thus, the comic-based teaching module developed is deemed feasible, practical, and effective for use in Hajj jurisprudence (fiqh) learning. The final product is a comic-based teaching module for Hajj jurisprudence learning designed to facilitate a more engaging, interactive, and easily understood learning process for students.